Effect of Rams, Incubation Time and Dilution Rate on The Motility and Longevity Characteristics of Merino Rams Spermatozoa - Ismaya (Ismaya) (Buletin Peternakan, 2006)
File lengkap ada dalam bentuk PDF dibawah ini